Which NADPH Oxidase Isoform Is Relevant for Ischemic Stroke? The Case for Nox 2 - Kahles, Timo (Mary Ann Liebert, Inc., 2013)
Significance and Recent Advances: Ischemic stroke is the leading cause of disability and third in mortality in industrialized nations. Immediate restoration of cerebral blood flow is crucial to salvage brain tissue, but only few patients are eligible for recanalization therapy. Thus, the need for alternative neuroprotective strategies is huge, and antioxidant interventions have long been studied in this context. Reactive oxygen species (ROS) physiologically serve as signaling molecules, but excessive amounts of ROS, as generated during ischemia/reperfusion (I/R), contribute to tissue injury. Critical Issues: Nevertheless and despite a strong rational of ROS being a pharmacological target, all antioxidant interventions failed to improve functional outcome in human clinical trials. Antioxidants may interfere with physiological functions of ROS or do not reach the crucial target structures of ROS-induced injury effectively. Future Directions: Thus, a potentially more promising approach is the inhibition of the source of disease-promoting ROS. Within recent years, NADPH oxidases (Nox) of the Nox family have been identified as mediators of neuronal pathology. As, however, several Nox homologs are expressed in neuronal tissue, and as many of the pharmacological inhibitors employed are rather unspecific, the concept of Nox as mediators of brain damage is far from being settled. In this review, we will discuss the contribution of Nox homologs to I/R injury at large as well as to neuronal damage in particular. We will illustrate that the current data provide evidence for Nox2 as the most important NADPH oxidase mediating cerebral injury. Antioxid. Redox Signal. 18, 1400–1417.